1999
DOI: 10.1038/sj.bjp.0702426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous administration of prostacyclin on regional blood circulation in awake rats

Abstract: 1 The eects of intravenous infusion of prostacyclin (PGI 2 , 0.1, 0.2, 0.3 and 1.0 mg kg 71 min 71 lasting 5 min) on regional blood¯ow and regional vascular resistance have been studied in awake rats using the radioactive microsphere method.2 The control values of blood¯ow to the heart, kidney, small intestine, hind limb muscle, pericranial skin and brain as well as the corresponding vascular resistance were not modi®ed by an i.v. infusion (0.1 ml min ) with corresponding reductions in blood¯ow. The low doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…Similar to the upper GI tract, an important mechanism for the onset of NSAIDs-induced small intestinal damage is the inhibition of COXs. Since PGs also play a crucial role in the maintenance of intestinal integrity by upregulating mucosal blood flow and mucus/fluid and regulating intestinal motility [53][54][55], PG deficiency subsequent to COX inhibition leads to the impairment of the mucosal defensive system in the small bowel. In an animal study, neither SC-560 (a selective COX-1 inhibitor) nor rofecoxib (a selective COX-2 inhibitor) alone caused intestinal damage, but their combined administration induced lesions.…”
Section: Pathophysiology Of Nsaids-induced Enteropathy Cox Inhibitionmentioning
confidence: 99%
“…Similar to the upper GI tract, an important mechanism for the onset of NSAIDs-induced small intestinal damage is the inhibition of COXs. Since PGs also play a crucial role in the maintenance of intestinal integrity by upregulating mucosal blood flow and mucus/fluid and regulating intestinal motility [53][54][55], PG deficiency subsequent to COX inhibition leads to the impairment of the mucosal defensive system in the small bowel. In an animal study, neither SC-560 (a selective COX-1 inhibitor) nor rofecoxib (a selective COX-2 inhibitor) alone caused intestinal damage, but their combined administration induced lesions.…”
Section: Pathophysiology Of Nsaids-induced Enteropathy Cox Inhibitionmentioning
confidence: 99%
“…Its main action in vivo is to inhibit aggregation and adhesion of platelets (Higgs et al, 1978;Murata et al, 1997). Prostacyclin has vasodilator properties and is suggested to contribute to hypercapnic and hypoxic cerebral hyperemia, but its role in regulation of vascular resistance under normal conditions has not yet been defined (Heinert et al, 1999;McCalden et al, 1984;Raczka and Quintana, 1999). Prostacyclin or its stabile analogues has been shown to increase cerebral blood flow, decrease extravasation of macromolecules and decrease edema formation following cerebral ischemia (Fukuyama et al, 1993;Pluta, 1994;Shima et al, 1995;Terawaki et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Early studies on PGI 2 indicated a reduction in cerebral blood flow after PGI 2 intravenous infusion in normotensive humans and rats [912], implicating a possible role in the maintenance of cerebrovascular tone. This is probably of importance since in cases of brain injury, PGI 2 may potentially be therapeutic.…”
Section: Introductionmentioning
confidence: 99%